Characters of external morphology used in Anolis taxonomy—Definition of terms, advice on usage, and illustrated examples - Köhler, Gunther (Zootaxa, 2014)
With the aim of establishing a reference for taxonomists, I describe and discuss characters of external morphology that have been used widely in descriptions of Anolis (sensu lato) species. For most characters, images are provided to illustrate the terms and definitions. Where appropriate, I give advice on how the counts and measurements should be done.